Great mimickers: Tumor like lesions of uterine corpus - Shetty, Divya Shekhar; Gosavi, Alka Vikas; Murarkar, Prashant Shankarrao; Sulhyan, Kalpana Ranjitsingh (International Journal of Health Sciences, 2020)
Objective: The objective of the study was to evaluate the relative occurrence of uterine corpus tumor-like lesions and to establish a clinicopathological correlation. Methods: A 5-year study was conducted on histopathologically diagnosed cases of tumor-like lesions of the uterine corpus. The lesions were classified according to the recent World Health Organization classification. Relevant clinical findings and histomorphologic details were noted and analyzed. Results: A total of 85 cases of tumor-like lesions were included in the study. Multiparous women (88.2%) were most commonly affected and endometrial polyp (89.4%) was the most common lesion. Endometrial polyp showed a definite predilection during the 3rd and 4th decades of life (56.6%) whereas Arias-Stella reaction was seen in pregnant women and squamous metaplasia was seen in peri and postmenopausal women. Patients with endometrial polyp presented mostly with heavy menstrual bleeding (HMB) (32%) and Arias-Stella reaction with HMB. Two cases of squamous metaplasia one presented with HMB and pain in the abdomen. Most of the endometrial polyps were single (90.8%) and sessile (68.4%), hyperplastic type (56.6%) and the adjacent endometrium were mostly atrophic (42.1%) or in proliferative phase (34.2%). The mean age in years of premenopausal women was 39.34 ± 5.01 and postmenopausal women were 62.66 ± 7.26. The mean size of the polyp, parity, number of polyps and association with leiomyoma was not significantly different between premenopausal and postmenopausal women. Adenomyosis was seen in 11 cases of the endometrial polyp. Conclusions: Although tumor-like lesions of the uterine corpus as the name suggests tend to mimic the tumors, certain clinical and histopathological features can help in making the accurate diagnosis and thus avoid unnecessary radical surgeries.